THE INFLUENCE OF BASIC TRAINING FOR PROSPECTIVE CIVIL SERVANTS BASED ON ACCELERATE EXPERIENTIAL SELF REGULATED (AES) LEARNING TO IMPROVE THE CORE VALUES OF STATE CIVIL APPARATUS AT THE HUMAN RESOURCES DEVELOPMENT AGENCY OF SUMATERA UTARA PROVINCE - Yamnur Mahlia; Arif Rahman; Yuniarto Mudjisusatyo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
ASN Core Value Module, (5) Material related to State Civil Apparatus core values, (6) Encouraging trainees to become lifelong learners and (7) reflection. The value of the feasibility test is 93% (material experts) very feasible, the value of 89% (media experts) very feasible, and the user 93.75% very good. The results of the effectiveness test The effectiveness test is seen from the N-Gain Score value for understanding ASN core values 85.10% (limited trial) and 82.86% (extensive trial results). While for the application of State Civil Apparatus core values, the N-Gain Score value is 83.61% (limited trial) and 82.93% (extensive trial results). Because the g value > 75 is in the effective category. The effectiveness of the Prospestic State Civil Apparatus basic training management model obtained a value of 93.75% with a very good category and the training program was assessed on average at 93.65% with a very good category. So it can be concluded that the AES Learning-based Prospective Civil Servants Basic Training Management Model is very effective in increasing the core values of State Civil Apparatus at the BPSDM of Sumatera Utara Province.